Autonomic Neuropathy—a Prospective Cohort Study of Symptoms and E/I Ratio in Normal Glucose Tolerance, Impaired Glucose Tolerance, and Type 2 Diabetes - Zimmerman, Malin; Pourhamidi, Kaveh; Rolandsson, Olov; Dahlin, Lars B. (Frontiers in Neurology, 2018)
Background Autonomic neuropathy in diabetes, in addition to causing a range of symptoms originating from the autonomic nervous system, may increase cardiovascular morbidity. Our aim was to study the progression of autonomic neuropathy, based on symptom score and evaluation of an autonomic test, in persons with normal and impaired glucose tolerance (IGT) and in patients with type 2 diabetes (T2D). Methods Participants were recruited in 2003/2004 with a follow-up in 2014. The participants´ glucose tolerance was categorized using oral glucose tolerance tests (OGTT). Symptoms were evaluated using an autonomic symptom score (ASS), ECG was used to test cardiac autonomic function based on the expiration/inspiration ratio (E/I ratio) , and blood samples were taken on both occasions. Results ASS scores were higher at follow-up in the T2D patients than in the NGT group (mean 1.211.30 vs. 0.790.7; p<0.05). E/I-ratio did not deteriorate more than could be expected as an ageing effect in well-controlled T2D. No relationship was found between E/I-ratio and HbA1c or ASS. Conclusions The presence of autonomic symptoms increased over time in T2D patients, but the symptoms did not correlate with the E/I ratio in this metabolically well-controlled cohort. Autonomic symptom scores can be a useful clinical tool when assessing the progression of autonomic dysfunction in patients with abnormal glucose metabolism.